PENGARUH VIRAL MARKETING DAN PERCEIVED ADVERTISING VALUE PADA PURCHASE INTENTION (Studi tentang perilaku Gen Z terhadap Produk Elektronik di TikTok Shop di Indonesia) - Supartha, Anak Agung Ayu Rika Putri; Putu Dhanan Kumaradewi M, Ni (Bajang Institute, 2025)
This study investigates the influence of viral marketing and perceived advertising value on purchase intention among Generation Z consumers toward electronic products on TikTok Shop in Indonesia. Using the Stimulus-Organism-Response (SOR) framework, the research explores how external marketing stimuli and consumer perceptions shape behavioral intentions. Data were collected from 110 Gen Z respondents aged 20–28 through an online survey distributed via Google Forms. Respondents were selected using purposive and convenience sampling methods, focusing on individuals who had purchased electronic products and been exposed to TikTok advertising. The data were analyzed using the PLS-SEM approach with SmartPLS 4.1. The findings reveal that both viral marketing and perceived advertising value have a positive and significant effect on Purchase intention. Among these, perceived advertising value had the stronger influence, indicating that informative, credible, and engaging advertising content enhances consumers’ willingness to purchase. These results emphasize the importance of developing value-driven advertising and viral marketing strategies to strengthen engagement and conversion among digital- native consumers on TikTok.